The thrombotic risk in Cushing’s syndrome—questions, answers, and the algorithm to consider in its assessment: part I—thrombotic risk not related to surgery - Bryk-Wiązania, Agata Hanna; Minasyan, Mari; Świątkowska-Stodulska, Renata; Undas, Anetta; Hubalewska-Dydejczyk, Alicja; Webb, Susan M.; Valassi, Elena; Gilis-Januszewska, Aleksandra (Frontiers in Endocrinology, 2024)
Introduction. Recently, it has been reported that there is a great diversity in strategies used for thromboprophylaxis in patients with Cushing's syndrome (CS). An aim of this review was to discuss these practices in light of the existing data on the thrombotic risk in patients with CS, and guidelines for medically ill patients.Methods. The 4 relevant topics and questions on thrombotic risk in CS were identified. The current guidelines on prevention and diagnosis of venous thromboembolism (VTE) were reviewed for the answers. An algorithm to consider in the assessment of the thrombotic risk in patients with CS was proposed.Results. To address both generic and CS-specific risk factors for VTE, the algorithm includes the stepwise approach consisting of Padua Score, urine free cortisol, and CS-VTE score, with no indication for routine thrombophilia testing in the prediction of an index VTE episode. Having confirmed VTE, selected patients require thrombophilia testing, to aid the duration of anticoagulant treatment. The separate part of the algorithm is devoted to patients with ectopic adrenocorticotropic hormone syndrome, in whom exclusion of VTE precedes introducing routine thromboprophylaxis to prevent VTE. The cancer-related VTE also prompts thromboprophylaxis, with the possible vessel invasion. The algorithm presents an unifactorial and multifactorial approach to exclude high bleeding risk, and safely introduce thromboprophylaxis with low-molecular-weight heparin. Summary. Our article is the first to present an algorithm to consider in the thrombotic risk assessment among patients with Cushing's syndrome, as a starting point for a broader discussion in the environment. A plethora of factors affect the VTE risk in patients with CS but no studies have conclusively evaluated the best thromboprophylaxis strategy so far. Future studies are needed to set standards of care.